Experimental and theoretical studies on the excess capacity of Photosystem II - Kana, Radek; Lazár, Dusan; Prásil, Ondrej; Naus, Jan (Photosynthesis research, 2002)
It has been recently suggested that compensatory changes in Photosystem II (PS II) electron turnover rates can protect photosynthesis from photoinhibition [Behrenfeld et al. (1998) Photosynth Res 58: 259-268]. We have further explored this feature of PS II using a rate electrode for simultaneous measurements of the steady-state rate of oxygen evolution and the oxygen flash yield depending on the background irradiance in both control and photoinhibited algal cells of Chlorella Böhm. Theoretical simulations based on the two-electron gate model agree qualitatively with experimental data if we assume an increase of the electron turnover rate in the remaining functional PS II centers of the photoinhibited sample. Our results confirm the hypothesis that the compensatory effect enables cells to maintain the maximal rates of photosynthesis even in the presence of moderate photoinhibition (decrease of up to 50% in the number of functional centers) and that the effect originates from the inner capacity of electron transport through PS II. The origin of the compensatory effect is briefly discussed.